An exploration into the stressors and coping strategies of parents caring for children living with Autism spectrum disorder - Baker, Robyn (Department of Social Development, 2021)
This study sought to understand the experiences and challenges of parents caring for a child living with autism spectrum disorder (ASD). A qualitative research design was used to explore the stressors faced, coping strategies used, and support mechanisms needed by parents caring for a child living with ASD within South Africa. Non-probability sampling was used to select 20 respondents, initially using purposive and then snowball sampling techniques, until the target sample size was reached and data saturation had occurred. Respondents consisted of South African mothers who care for a child living with ASD, and who live in Cape Town, Johannesburg, or Durban. Data was collected with the use of semi-structured one-on-one interviews, and was analyzed according to Tesch's (1990) eight steps of analysis. The study found that there were various practical stressors for respondents regarding caring for a child living with ASD. This included the stressors of managing their child's difficult behaviours, respondents' high levels of anxiety as a result of these behaviours, and difficulties communicating with their child. Stressors also included the high cost of care and interventions, difficulty finding appropriate schooling, and the need to consult multiple professionals before receiving the diagnosis. The respondents' psychological stressors included experiencing grief and loss once their child was diagnosed, hurt from other's lack of understanding of ASD, and their concerns about their child's future. Various coping mechanisms were found to be used by respondents, including accepting the child with their diagnosis, increasing in patience and empathy, and attempting to manage and prevent their child's difficult behaviours. Another coping mechanism was to utilize a blend of interventions, for example Occupational and Speech Therapy, which catered to their child's unique ASD-presentation. Support mechanisms that were found to be beneficial to respondents were informal and consisted of support from family and from other parents caring for a child with ASD. This study concluded that caring for a child with ASD has many challenges, especially when one is the child's parent and primary caregiver. It also concluded that respondents displayed resilience towards these challenges by utilizing various coping and support mechanisms available to them. Numerous recommendations arose from this study, the most salient of which was for health care professionals (HCPs), which included social workers, as well as parents caring for a child living with ASD to educate themselves and others with regards to ASD. Another recommendation was for HCPs to link these parents with affordable and appropriate education and intervention options for their children.